Self-Regulated Learning Strategies for The Challenges of Learning During Pandemic - Teo Siew Hway (Asia Pacific Journal of Social Science Research, 2022)
Higher education institutions have long been thought to be more vulnerable to the COVID-19 virus community spread, and nearly all schools and universities have abandoned face-to-face academic activities in favour of alternate teaching techniques. This quantitative study examines foundation students’ self-regulated learning abilities and the extent to which self-regulation skills occur in the online learning context during the COVID-19 pandemic. Self-regulation skills awareness is critical in foundation programme education. These abilities will prepare students to learn effectively in their future studies, especially in a blended learning environment in higher education. This study looked at six sub-constructs of self-regulated learning skills in the context of online learning, including goal-setting, environmental structuring, task methods, time management, help-seeking, and self-evaluation. Fifty foundation students from Universiti Kuala Lumpur MICET participated in this study. Most students reported using goal-setting, time management, environmental structuring, and help-seeking in an online learning environment. Overall, the findings showed that Foundation students’ self-regulated learning skills were all above the midpoint of the fifty percent, except task techniques and self-evaluation, which are still minor. The study comes to a close with a few observations and suggestions